Improvement of cisplatin-induced injuries in sperm quality, oxidant-antioxidant system and hystological structure of the rat testis by ellagic acid - Türk, G; Ateşşahin, A; Sönmez, M; Çeribaşı, Ao; Yüce, A (My University, 2006)
Objective: To investigate whether ellagic acid (EA) has a possible protective effect against cisplatin (CP)-induced negative changes in epididymal sperm characteristics and the histologic structure of testis and prostate associated with oxidative stress in rats. Design: Experimental study. Setting: Fırat University Medical School Experimental Research Center, Elazı g, Turkey. Patient(s): Eight-week-old adult male Sprague Dawley rats (n ¼ 24). Intervention(s): Cisplatin was administered to rats at a single dose of 7 mg/kg IP. Ellagic acid was administered both separately and simultaneously with CP by gavage daily for 10 days at the dose of 10 mg/kg. Main Outcome Measure(s): Reproductive organ weights, epididymal sperm characteristics, and histopathologic structure of testes and ventral prostate were determined along with malondialdehyde (MDA) and glutathione (GSH) levels and glutathione-peroxidase (GSH-Px) and catalase (CAT) activities of plasma, sperm, and testicular tissue. Result(s): Ellagic acid ameliorated the CP-induced reductions in weights of testes, epididymides, seminal vesicles, and prostate along with epididymal sperm concentration and motility. Additionally, EA decreased the CP-induced increments in abnormalities of sperm. Whereas CP increased the MDA levels of plasma, sperm, and testicular tissue, it decreased the GSH-Px and CATactivities in the study samples compared with the control group. The administration of EA to CP-treated rats decreased the MDA level and increased GSH-Px and CATactivities in these samples. Cisplatin caused degeneration, necrosis, interstitial edema, and reduction in germinative cell layer thickness and rarely reduction in spermatogenic activity in some seminiferous tubules. The CP-induced changes in histopathologic findings of testis were partially reversed by treatment with EA. No significant changes were observed in the histopathologic structure of the prostate among any of groups. Conclusion(s): Ellagic acid has a protective effect against testicular toxicity caused by CP. This protective effect of EA seems to be closely involved with the suppressing of oxidative stress.
Bildiri - Yayımlanmamış
Bildiri - Kongre ve Sempozyum
Keywords: Cisplatin ellagic acid oxidative stress sperm characteristics testis rat